Alokasi Pendapatan Usahatani Rumput Laut di Kota Kendari - Makmur, Ghina Rahmayanti; Surni, Surni; Limi, Muhammad Aswar (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2019)
This research was conducted with the aim to determine the allocation of income for seaweed farming. The research was conducted in Sambuli Village, Kendari City, towards seaweed farmers who are still cultivating seaweed. The variable in this study is the allocation of seaweed farming income for business continuity within one month. The allocation of income obtained from seaweed farming was analyzed using the formula of income allocation. Based on the results of the analysis, it is known that the entire income of seaweed fishermen is allocated for food and non-food needs so that the allocation of income for the sustainability of seaweed farming becomes smaller. Kendari City government participation is needed to prevent environmental damage that threatens the sustainability of natural resources on the coast of Kendari Bay which causes the production and income of seaweed farmers to decline and threaten the sustainability of seaweed farming